Shahr-i Sokhta Excavations - Ascalone, Enrico (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
Following the surface surveys conducted during January and February 2017, the location of workshop No. 33 was selected for research and excavations to obtain information about the stratigraphic and topographic status of this part of the site. Following the numbering of excavated workshops by Shahr-e Sokhteh Archaeological Group under the supervision of Seyed Mansour Seyed Sajjadi, this workshop has been read with number 33 (Sajjadi, 2003, 2005, 2014). Our research goals are consistent and meaningful. This choice was specifically aimed at researching when the burnt city reached its widest size during the second and third periods of settlement.